Conditions for Removal of Arsenic Fromnon - Ferrous Metal Wastewater in the Form of Precipitates - M. Czaplicka; K. Jaworek; L. Bratek (Canadian Institute of Mining, Metallurgy and Petroleum, 2014)
Methods for arsenic compound removal from aqueous solutions include processes such as: coagulation, adsorption, membrane techniques, electrochemical and biotechnology techniques. Advanced oxidation using both UV radiation and strong oxidizing agents such as ozone and hydrogen peroxide may also decompose these compounds. It is known that effluents from metallurgical processes contain inorganic arsenic compounds in addition to the organic compounds such as: dimethylarsinic acid and phenylarsonic acid. This paper presents the conditions that lead to the formation of deposits containing mainly arsenic, such as pH, the wavelength of the radiation and the type of oxidant, for this type of effluent.